Analisis Regresi Loyalitas Pengguna E-Commerce Bukalapak Dengan Variabel Technology Acceptance Model - Gusta Irfan Windana; Sri Hariyati Fitriasih; Tri Irawati (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
Online shopping is the activity of purchasing goods and services through the internet. Through online shopping, customers can preview the goods and services they want to buy on the web promoted by the seller. E-commerce and online shopping activities are becoming very popular among internet users. Customers who shop online can be classified into different purchase orientations. The purchasing orientation can influence both user loyalty Behaviour and intentions in shopping online on Bukalapak as e-commerce. Based on the results of a survey by the Indonesia Internet Service Providers Association (APJII) regarding the profile of Indonesian internet users in 2018, 34.60 per cent of the reasons for not shopping online are afraid of fraud and 21.5 per cent of them stated that they cannot directly buy the goods. The explanation above indicates that user loyalty is still quite low in online shopping. Through the Perceived Usefulness towards the loyalty Behaviour of Bukalapak users, the result of the research proves the first to fourth hypotheses that all Technology Acceptance Model (TAM) variables have a positive and significant effect on the loyalty Behaviour of Bukalapak users and through the TAM test, it is concluded that all variables used in conducting an information system analysis, most respondents answered strongly agree with the percentage of 40% and agree with the percentage of 46.50%..